1967
DOI: 10.1017/s0022172400045915
|View full text |Cite
|
Sign up to set email alerts
|

The incidence ofHerpesvirus hominisantibody in the population

Abstract: Sera from 1029 individuals, 864 from Edinburgh and 165 from Oxford, have been examined for the presence of antibodies toHerpesvirus hominis. The results of the smaller Oxford survey did not reveal a higher incidence of antibody where direct comparison was possible with those from Edinburgh.The incidence of both complement-fixing and neutralizing antibodies in the sera from 710 people in Edinburgh with ages varying from 1 month to 92 years was compared with the more complete of the earlier surveys, and in parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
1
2

Year Published

1969
1969
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(39 citation statements)
references
References 20 publications
(28 reference statements)
3
33
1
2
Order By: Relevance
“…To preserve low titre antibodies sera were not heat-inactivated Toniguchi, 1964, 1966;Heineman, 1967) (Table IV). (Buddingh et al, 1953;Yoshino et al, 1962;Smith et al, 1967). A four-fold rise in the level of serum antibody is characteristic of a primary infection but patients with recurrent herpetic infections usually exhibit a permanently high level of antibody (Scott et al, 1952;Scott, 1957).…”
Section: Treatmentmentioning
confidence: 99%
“…To preserve low titre antibodies sera were not heat-inactivated Toniguchi, 1964, 1966;Heineman, 1967) (Table IV). (Buddingh et al, 1953;Yoshino et al, 1962;Smith et al, 1967). A four-fold rise in the level of serum antibody is characteristic of a primary infection but patients with recurrent herpetic infections usually exhibit a permanently high level of antibody (Scott et al, 1952;Scott, 1957).…”
Section: Treatmentmentioning
confidence: 99%
“…In Japan and other industrial countries, an increase in the seronegative rate in young adults has been elucidated (4,6,8,9). We reported previously that the rate of seropositive young adults had decreased in Fukuoka, though the positive rate was 82% in the 11-to 20-year-old group in Manila (3).…”
mentioning
confidence: 94%
“…All the sera were collected from the following sources in the year 1988 from the residents of Yogyakarta, Indonesia: (1) 86 sera from patients admitted to Panti Rapih Hospital, Yogyakarta; (2) 59 sera from pregnant women in the ObstetricsGynecological Clinic of Dr. Sardjito Hospital; (3) 20 sera from patients of the Dermato-Venereology Clinic of Dr. Sardjito Hospital; (4) 129 sera from healthy prostitutes in Yogyakarta; (5) 64 sera from healthy massagers in Yogyakarta; (6) 39 sera from healthy tourist guides in Yogyakarta; (7) 90 healthy blood donors in Yogyakarta. Sera of individuals younger than six months and of patients suspected of having herpetic infections from clinical manifestations were not included.…”
mentioning
confidence: 99%
“…In addition to these points, since this method is simple and faster than other methods, the PHA test is considered to be a useful method for measuring antibodies to HSV-1, though antibody to herpes simplex virus type 2 cannot be distinguished from that of HSV-1 by this PHA test. In Japan and other industrial countries, an increase in the seronegative rate in young adults has been demonstrated (5,7,9,10) . We reported previously that the rate of seropositive young adults has decreased in Fukuoka, though the positive rate was 87% in the 11-to 20-year age group in Busan (4) .…”
mentioning
confidence: 99%
“…The incidence of antibodies to HSV-l increases with age but varies considerably with socioeconomic conditions (3,5,7,9,10) . Our group has reported a difference in age distribution of antibodies to HSV-l among the sera from Fukuoka, Manila, Busan, and Indonesia (1,4) .…”
mentioning
confidence: 99%